Assessment On Heavy Goods Vehicle Conspicuity Based On The Road Transport Act 1987 - Yahya, Siti Aishah (Universiti Sains Malaysia, 2019)
In Malaysia, accidents that involve collisions with rigid and articulated trucks were mainly related to the conspicuity issue. Conspicuity refers to the visual characteristics of other motor vehicles which direct a driver's attention to them. The effect of conspicuity is associated with the rear markings and lighting components on the heavy goods vehicles (HGV). Thus, increasing the visibility and conspicuity of the rear side of heavy goods vehicles may help to enhance safety measures that all GV drivers encounter. The study was conducted for three consecutive days at Jawi Toll Plaza, Nibong Tebal, Pulau Pinang from 9.00 a.m. to 5.00 p.m. The first objective of the study is to analyse the percentage of marking requirements that comply with the MS 828:2011. The colour and pattern of painted surfaces, size, lighting system, reflectorization, and fluorescent markings determine the conspicuity of a vehicle. The retroreflective marking needs to be installed on heavy vehicles for better visibility. The highest compliance level of marking requirement was 96%, which is a box truck, two axles. Meanwhile, other categories were between 17% to 91%. Rear end marking type 5 was not being installed by any HGVs, although all trucks and trailers with maximum gross vehicle weight (GVW) of 3500kg and above were compulsory to be marked with type 5 starting on 1 July 2019. In addition to rear markings, visibility of HGVs could be enhanced should they be equipped with lighting components as being required by laws. The second objective of the study is to analyse the percentages of lighting components installations on HGV rear-side that comply with the MS ISO 303:2004. Results show that 93% of box trucks two axles had installed rear lighting components that adhere to the standard. In conclusion, only a box trucks two axles have the highest percentage of compliance with the standard requirement of rear-end marking and lighting component.